Improving Fourth-Grade Students' Conceptual Understanding in Social Science through the Problem-Based Learning (PBL) Model at SDN Banyuajuh 9 - Aviqoh Azza An-Nadwah; Gisca Julya Hidayah; Elsa Dwi Yulinda; Ikhtiatus Sholihah; Agung Setyawan (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2026)
This study emerged from concerns about the weak conceptual understanding of science among fourth-grade students at SDN Banyuajuh 9. Traditional teacher-dominated instruction had limited students’ involvement, leaving many unable to achieve learning mastery. To transform the classroom atmosphere into a more interactive and meaningful environment, the Problem Based Learning (PBL) model was introduced. Using a Classroom Action Research framework, the study was conducted in two cycles consisting of planning, implementation, observation, and reflection stages, involving 18 learners. Data were gathered through tests, classroom observations, and documentation, with success measured by achieving at least 80% classical mastery. The outcomes showed remarkable progress: mastery improved from 16.7% in the pre-cycle stage to 44.4% in Cycle I, and finally soared to 94.4% in Cycle II. These findings highlight that PBL not only strengthens conceptual understanding but also inspires students to become more active and enthusiastic participants in learning.